IMPLEMENTASI STRATEGI PENINGKATAN KEPUASAN PASIEN DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Jon Piter Sinaga; Harris Rambey; Sri Melda Bangun; Ika Nur Saputri (JURNAL PENGMAS KESTRA (JPK), 2021)
The concept of service quality related to patient satisfaction can be determined by five elements, namely responsiveness, assurance, tangible, empathy and reliability. Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares it with what is expected. Fair and equitable services will be able to lead to satisfaction because the community at this time has begun to be critical in assessing services, especially in the health sector. This community service activity is in the form of measuring the quality of health services as an implementation of patient improvement strategies. Measurement of patient satisfaction is done through filling out a questionnaire sheet which is an instrument for measuring inpatient satisfaction, by patients who are going home. Quality services that provide a health service that is truly in accordance with the needs of the patient and refers to the level of service perfection. The more perfect the health services provided, the better the quality of health services.